Odpowiedzi

2010-02-10T16:17:53+01:00
A) A=(-5;0) B=(0;-2) C=(2;2)
|AB|*2=(0+5)*2+(-2-0)*2=25+4=29
|BC|*2=(2-0)*2+(2+2)*2=4+16=20
|AC|*2=(2+5)*2+(2-0)*2=49+4=53

|AB|^2+|BC|^2<|AC|^2
Trójkąt nie jest prostokątny



b) A=(4;-1) B=(1;5) C=(-4;3)
|AB|*2=(1-4)*2+(5+1)*2=9+36=45
|BC|*2=(-4-1)*2+(3-1)*2=25+4=29
|AC|*2=(-4-4)*2+(3+1)*2=64+16=80

|AB|*2+|BC|*2<|AC|*2
Trójkąt nie jest prostokątny

C) A=(-3;-1) B=(6;-4) C=(7;-1)
|AB|*2=(6+3)*2+(-4+1)*2=81+9=90
|BC|*2=(7-6)*2+(-1+4)*2=1+9=10
|AC|*2=(7+3)*2+(-1+1)*2=100+0=100

|AB|^2+|BC|^2=|AC|^2
Trójkąt jest prostokątny
2010-02-10T16:38:21+01:00
A)
A=(-5,0) B=(0,-2)
|AB|=√(-5-0)²+(-2-0)²
|AB|=√29
B=(0,-2) C=(2,2)
|BC|=√(0-2)²+(-2-2)²
|BC|=√20
C=(2,2) A=(-5,0)
|CA|=√(2+5)²+(2-0)²
|CA|=√53
|AB|²+|BC|²=|CA|²
29+20≠53
Odp. Nie
b)
A=(4,-1) B=(1,5)
|AB|=√(4-1)²+(-1-5)²
|AB|=√45
B=(1,5) C=-4,3)
|BC|=√(1+4)²+(5-3)²
|BC|=√29
C=-4,3) A=(4,-1)
|CA|=√(-4-4)²+(3+1)²
|CA|=√80
|AB|²+|BC|²=|CA|²
45+29≠80
Odp. Nie
c)
A=(-3,-1) B=(6,-4)
|AB|=√(-3-6)²+(-1+4)²
|AB|=√90
B=(6,-4) C=(7,-1)
|BC|=√(6-7)²+(-4+1)²
|BC|=√10
C=(7,-1) A=(-3,-1)
|CA|=√(7+3)²+(-1+1)²
|CA|=√100
|AB|²+|BC|²=|CA|²
90+10=100
Odp. TAK